Long-term mental health change patterns in ICU survivors: a four-year comparative follow-up from the SMAP–HoPe study - Takeshi Unoki; Tomoki Kuribara; Sakura Uemura; Mayumi Hino; Masako Shirasaka; Yuko Misu; Takumi Nagao; Mio Kitayama; Junpei Haruna; Masahiro Yamane; Keiko Atsumi; Miyuki Sagawa; et al. (Journal of Intensive Care)
Abstract Background Post-intensive care syndrome (PICS) encompasses persistent physical, cognitive, and psychological impairments in individuals following intensive care unit (ICU) discharge. The short-term mental health impacts of PICS have been previously examined; however, long-term change pattern remain inadequately understood. In this study, we aimed to determine the prevalence of mental health disorders in individuals at 4 years post-ICU discharge, compare prevalence rates between 1 and 4 years, and identify change patterns and associated factors. Methods In this 4-year follow-up study of the SMAP–HoPe study (754 ICU survivors from 12 Japanese ICUs were originally examined in the SMAP–HoPe study), we included participants from seven ICUs who completed mental health assessments using the Hospital Anxiety and Depression Scale and Impact of Event Scale-Revised at both 1- and 4-years post-ICU discharge. Growth mixture modeling was employed to identify distinct change patterns for anxiety, depression, and post-traumatic stress disorder (PTSD). Results Among the 319 eligible participants, 223 (70.0%) provided responses. The prevalence of depression significantly increased from 24.7% at 1 year to 32.7% at 4 years (p = 0.021), whereas that of anxiety increased from 15.3% to 21.6% (p = 0.049). PTSD prevalence decreased from 5.1% to 2.7% (p = 0.549). Distinct change patterns were observed for anxiety—minimal (scores < 4) and decreasing, mild (scores ≥ 4) and increasing, and moderate (scores ≥ 8) and stable; for depression—minimal (scores < 4) and stable, mild (scores ≥ 4) and increasing, and moderate (scores ≥ 8) and stable; and for PTSD—minimal (scores < 4), mild (scores ≥ 4), and moderate (scores ≥ 10) symptoms that remained stable. Participants with higher education had a lower risk of exhibiting the moderate-stable depression change patterns (adjusted odds ratio: 0.25, 95% confidence interval: 0.09–0.68, p = 0.006). Conclusions Mental health disorders in ICU survivors persist for a long term, with the prevalence of depression increasing over 4 years. Multiple change patterns were observed for each disorder, suggesting various progression courses. Participants with high education were protected from severe depression and its change patterns. These findings highlighted the importance of extended follow-up care and individualized interventions based on the change patterns and associated predictors.